Computer Interaction in the Use of Radiometric Calibration for the Cassini Space Flight Probe - Brown, Kenneth A. (International Journal of Virtual Reality, 1996)
In the area of Radiometric Calibration for Space Flight Hardware, there is a need for accurate data manipulation and analysis. At the Jet Propulsion Laboratory in Pasadena, CA, there is an advanced system of calibration and analysis of spacecraft data designed by the Planetary Instruments Group of the Space Instruments Implementation. We examine a problem with the user interface. As data is downloaded in this system, it must be physically examined for "good" and "bad" data points. This paper describes how to make this process more efficient. With the use of a light pen or touch-screen CRT the choice of data points can be quickly and accurately chosen or discarded. The article provides a description of the process of data acquisition as well as contributions toward the design of a more "friendly" data calibration procedure.